Virtual Keyboard (International Journal of Engineering and Computer Science, 2017)
This paper presents a virtual keyboard technology based on ultrasonic sound technique. Virtual Keyboard can be defined as touch typing device which enhances and enables the communications through virtual interface technology. It doesn’t have a physical appearance like conventional keyboard. Instead it uses a laser projection module to display the layout of keyboard. It is actually a key-in device, which can be implemented in space saving situations and as well as in hostile environments as the utilization of conventional keyboard is limited there. When system is powered ultrasonic sensor continuously emits signals, which then used to identifying the characters. The corresponding character will then displayed using arduino and Bluetooth module.